PELATIHAN PEMBUATAN BAHAN AJAR DIGITAL MENGGUNAKAN APLIKASI KVSOFT FLIPBOOK DAN WEB ANYFLIP DI SMP NEGERI 41 PADANG - Widya Widya; Zaturrahmi Zaturrahmi; Desy Eka Muliani; Ena Suma Indrawati; Yusmanila Yusmanila; Yeni Nurpatri (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
Technological developments have brought changes in the field of education. One of these changes is the provision of digital teaching materials to support online learning. Teachers as facilitators in education need to adapt to these changes. SMP Negeri 41 Padang views that there needs to be an increase in the ability of teachers to prepare teaching materials, especially in the form of digital teaching materials. Therefore, the team from physics education of STKIP Adzkia carried out community service in the form of training on making digital teaching materials using the kvsoft flipbook application and anyflip web for teachers of SMP Negeri 41 Padang. The service activities carried out for the teachers of SMP Negeri 41 Padang City are in the form of training on the development of Digital Teaching Materials using the flipbook and wb anyflip applications. This training has a significant impact on teachers in preparing digital teaching materials to provide teaching materials. This training received a good response from the school, both the principal and the teacher council. The principal welcomes this activity because this activity can improve teachers' ability to prepare quality materials and the times' demands. The teachers also found it very helpful in preparing teaching materials through this training.